Small intragenic deletion in FOXP2 associated with childhood apraxia of speech and dysarthria. Issue 9 (5th August 2013) - Turner, Samantha J; Hildebrand, Michael S.; Block, Susan; Damiano, John; Fahey, Michael; Reilly, Sheena; Bahlo, Melanie; Scheffer, Ingrid E.; Morgan, Angela T.
Abstract Relatively little is known about the neurobiological basis of speech disorders although genetic determinants are increasingly recognized. The first gene for primary speech disorder was FOXP2, identified in a large, informative family with verbal and oral dyspraxia. Subsequently, many de novo and familial cases with a severe speech disorder associated with FOXP2 mutations have been reported. These mutations include sequencing alterations, translocations, uniparental disomy, and genomic copy number variants. We studied eight probands with speech disorder and their families. Family members were phenotyped using a comprehensive assessment of speech, oral motor function, language, literacy skills, and cognition. Coding regions of FOXP2 were screened to identify novel variants. Segregation of the variant was determined in the probands' families. Variants were identified in two probands. One child with severe motor speech disorder had a small de novo intragenic FOXP2 deletion. His phenotype included features of childhood apraxia of speech and dysarthria, oral motor dyspraxia, receptive and expressive language disorder, and literacy difficulties. The other variant was found in a family in two of three family members with stuttering, and also in the mother with oral motor impairment. This variant was considered a benign polymorphism as it was predicted to be non‐pathogenic with in silico tools and found in database controls. This is the first report of a small intragenic deletion of FOXP2 that is likely to be the cause of severe motor speech disorder associated with language and literacy problems. © 2013 Wiley Periodicals, Inc.